Association between Methylmalonic Acid and Abdominal Aortic Calcification in Adults: A Cross-Sectional Study - Jun Chen; Yingwen Lin; Zhonghua Teng; Zhibin Lin; Junrui Li; Qingchun Zeng (Cardiovascular Innovations and Applications, 2024)
Objective: Methylmalonic acid (MMA) buildup has recently been suggested to contribute to the onset of both age-related conditions and cardiovascular disorders. This research was aimed at examining the link between MMA and abdominal aortic calcification (AAC). Methods: Data from the 2013–2014 National Health and Nutrition Examination Survey (NHANES) were analyzed. Serum MMA levels were determined through LC-MS/MS, and MMA levels 250 nmol/L or above were considered high. Dual-energy X-ray absorptiometry was used to assess the presence of AAC. Logistic regression analysis was performed after propensity score matching (PSM) to study the relationship between MMA and AAC. Results: A total of 2483 participants were involved in this study. To eliminate large differences between the AAC and non-AAC groups, 1:1 PSM was performed. Logistic regression analysis indicated that participants with high MMA levels had a significantly greater likelihood of experiencing AAC than those with low MMA levels (OR: 1.38, 95% CI: 1.01–1.90, P = 0.046). No statistically interaction effects between AAC and BMI or the estimated glomerular filtration rate (eGFR) were observed in subgroup analyses. Conclusion: Our study indicated a significant association between high serum MMA levels and AAC incidence.